2011
DOI: 10.1007/s11605-010-1366-9
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Mortality After Non-hepatic General Surgery in Patients with Liver Cirrhosis: an Analysis of 138 Operations in the 2000s Using Child and MELD Scores

Abstract: Our results demonstrate that perioperative mortality remains high in patients with liver cirrhosisundergoing general surgery, especially in emergent situations. Patients with poor liver function and/or need for blood transfusions even had a very high mortality. In our experience, the Child score (together with other variables) independently correlates with perioperative mortality in emergent operations whereas the MELD score was inferior in predicting the outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
96
3
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(113 citation statements)
references
References 36 publications
7
96
3
7
Order By: Relevance
“…In fact, in the previously mentioned study [29], Jeong reported that the presence of chronic liver disease effects the development of post-operative complications (chronic hepatitis OR 2.4; liver cirrhosis class A OR 8.4; liver cirrhosis class B OR 9.38). Similar results were found by Neef [30] in recent retrospective series of 138 non-hepatic abdominal operations in patients with liver cirrhosis: overall and surgical morbidity rate were 64 and 47 % even in elective surgery, therefore liver cirrhosis must be considered as a high impact risk factor for all kind of abdominal surgery.…”
Section: Discussionsupporting
confidence: 84%
“…In fact, in the previously mentioned study [29], Jeong reported that the presence of chronic liver disease effects the development of post-operative complications (chronic hepatitis OR 2.4; liver cirrhosis class A OR 8.4; liver cirrhosis class B OR 9.38). Similar results were found by Neef [30] in recent retrospective series of 138 non-hepatic abdominal operations in patients with liver cirrhosis: overall and surgical morbidity rate were 64 and 47 % even in elective surgery, therefore liver cirrhosis must be considered as a high impact risk factor for all kind of abdominal surgery.…”
Section: Discussionsupporting
confidence: 84%
“…96 In yet another study, perioperative mortality rates based on CTP stage were 10%, 17%, and 63% while similar rates at MELD of <10, 10-15, and >15 were 9%, 19%, and 54% respectively. 97 Amongst both the studies, CTP stage emerged better predictor of perioperative mortality compared to MELD score. In contrast, integrated MELD score was superior to CTP stage for predicting postoperative mortality.…”
Section: Comparing Model For End-stage Liver Disease and Child-pugh-tmentioning
confidence: 97%
“…The risk of perioperative death is markedly increased by cirrhosis due to any cause, [3][4][5] and cirrhosis is also associated with increased post-operative complications following cardiac surgery, [6][7][8][9] including increased rates of sepsis and bleeding. Serum bilirubin has been found to correlate with operative mortality and with the presence of cardiac cirrhosis in patients with primary pulmonary hypertension undergoing heartlung transplantation.…”
mentioning
confidence: 99%